The Processes of Import Substitution in the Agro-Food Sphere: Success or Failure? - Belova, Tatyana Nikolaevna (Economy of Regions, 2019)
The article is aimed at assessing the results of the protectionist policy in the agro-food sphere. The consumer food market depends on the import substitution in agriculture. Apparantly, it is erroneous to build a modern model of the agro-food market on the basis of export of cheap agricultural raw materials (grain) and import of expensive commodities. I found evidence to support this hypothesis in the works of foreign and domestic scientists. As a method I use the tools of statistical analysis. The empirical base of the study is represented by statistical material on export, import and domestic production for the period from 2012 to 2017 both in the country and in a typical region in the context of foreign trade (Ryazan region). The results of the study have showed the imbalance and irrationality of Russian export, import, domestic production and consumption. Since August 2014 agricultural producers have received several preferences for the growth of production: an embargo on food imports, government support and the weakening of the national currency. On the other hand, consumer demand decreased due to rising prices and lower incomes. The outstripping rise in food prices and the increase in the share of food expenditures in household budgets reflect an uneven state of the market. A detailed analysis of the situation in the regional markets has shown that the decline in consumer demand and saturation of local markets with imported products leads to an escalation of the problem of domestic products sales. The results of import substitution policy at the regional level should be measured in terms of economic access to food and per capita consumption. As a tool for the regulation of agro-food markets I propose to use the model of optimal placement of agricultural production. The results of the study can be applied in the development of state economic policy for regulating agro-food markets.